Observational study on histopathology of male anterior urethral stricture: Toward better understanding of stricture pathophysiology - Kashinath V Thakare; Tappa Mahammad Mustaq Rasool; Abhiram Kucherlapati; Ifrah Ahmad Qazi; Veda Murthy Reddy Pogula; Mude Sai Priyanka (Asian Journal of Medical Sciences, 2023)
Background: Stricture urethra is generally limited to anterior urethra. At present, there are only a few studies which focus exclusively on the histopathology of stricture urethra disease. Aims and Objectives: The aims of this study were to assess the urethral stricture pathology specimens for determining the severity of chronic inflammation and characteristics of stricture, demographics, and patient-reported outcome measures in patients with inflammatory and non-inflammatory strictures. Materials and Methods: This was a prospective and observational study done on 60 male patients of anterior urethral stricture disease who underwent excision biopsy of stricture during urethroplasty. Pre-operative urinary symptoms assessment was done with a questionnaire provided to all patients and data maintained to assess patient-reported outcomes in inflammatory and non-inflammatory stricture urethra. Cohorts comprising strictures with no inflammation, mild, and moderate to severe inflammation were developed and stricture, the patient characteristics were compared. Results: In a total of 60 histopathological stricture specimens, there was no inflammation in 40%, mild and moderate inflammation was in 28% and 3.3%, respectively. Lichen sclerosis-related strictures had moderate to severe inflammation and most of the strictures were in bulbar urethra (51.6%). Patients with BXO changes showed more inflammation. In patients with inflammatory strictures, hesitancy, straining, and stream were statistically more compared to non-inflammatory strictures. Idiopathic is the most predominant etiology for stricture which showed no inflammation. Conclusion: Histopathological analysis of urethral stricture showed significant tissue heterogeneity in clinically similar strictures. Chronic inflammation was commonly found in stricture specimens indicating active antigen presentation for underlying pathology and patients with inflammatory strictures reported worse health outcomes.